The use of the Google Forms platform in academic research: Experience report (Research, Society and Development, 2020)
Objective: To describe the use of the Google Forms platform as a research method. Methodology: This is an experience report lived by student and teacher, in which he obtained as a method the use of the Google Forms platform as an online research tool. Experience report: The collection of data through the online questionnaire that the Google Forms Platform has allowed to experience significant experiences in view of the distance between the participants, thus being able to obtain a significant number of participants from different locations throughout the national territory. Conclusion: It is important that teachers and students take ownership of this Google tool, as it has great potential in relation to distance research and has a wide scope of scope, so that they can come to innovate in their practices.